Implementation of sensor fusion for an anaerobic biogas digester using domestic market waste - Tsulutsya, F.B.; Budiarto, H.; Romadhon, A.S. (Universitas Mataram, 2024)
Domestic market waste is ranked second as the largest producer of organic waste in several regions in Indonesia. This lack can be a valuable thing. For example, alternative energy can be made possible through organic waste, one example is biogas. Vegetable and fruit waste that is produced daily by the market has great potential to be used as a substrate for making biogas, which can later be used as an alternative energy source. By adding other substrates such as methane (CH4), which can be obtained from agricultural waste such as cow dung, which is abundantly available in various regions, these two types of waste can be processed into biogas. The method for extracting biogas here is an anaerobic biogas digester. To maximize biogas through processed waste, two starters are used in the form of EM4 and yeast. The effect of the yeast type starter can maximize CH4 yields, which can be proven by the results of the two types of digesters, namely with yeast 192.56 Ppm while with EM4 ¬93.05 Ppm. In practice, in order to analyze the gas results, the researchers implemented an MQ2 gas sensor and thermocouple. Through sensor fusion, the best methane value can be seen at 192.56 Ppm with a temperature of 34˚ Celsius, which was obtained through fermentation for 30 days. Through this, the benefits obtained are not only reducing waste, but also renewable energy can be obtained.